COVID-19 and Climate-Smart Health Care : Health Sector Opportunities for a Synergistic Response to the COVID-19 and Climate Crises - World Bank (World Bank, Washington, DC, 2021)
The emergence of the Coronavirus disease 2019 (COVID-19) pandemic has brought with it a sharp focus on public health services and health systems as well as shed light on the chronic lack of capacity to manage emerging public health risks. Climate change further exacerbates this challenge. In combination with COVID-19, the climate crisis presents a clear and present risk of disrupting and overwhelming health systems, health care facilities, and the health care staff upon which these systems rely. This risk is of particular concern in those settings with already weak health systems, leadership challenges, insufficient resources, and limited capacities. Despite these concerns, the collective global effort to respond to COVID-19 and recover from it also presents important opportunities for implementing profound cross-cutting efforts within the health sector to tackle both the pandemic and the climate crisis. This report provides a framework that builds on the World Bank’s climate-smart health care approach and integrates the World Bank’s multiphase programmatic approach (MPA) into the global COVID-19 response. It is intended to guide ongoing as well as pipeline activities and investments targeted at the pandemic, with a view to enabling the health sector to leapfrog toward climate-smart universal health coverage (UHC).